The Songwriting Style of Thanakrit Panichwit - Chalermsub, Supawarat (Journal of Humanities and Social Sciences Suratthani Rajabhat University, 2023)
The research objective is to study the rhythmic language used in writing the songs of Thanakrit Panichwit. Qualitative research was conducted. There were four studio albums consisting of thirty-one songs by Thanakrit Panichwit, who is the only composer. The analysis of the songs of Thanakrit Panichwit employs the concept of language style, focusing on word usage, sentence usage, and the use of images. The results of the descriptive data analysis are presented. The research results found that Thanakrit Panichwit’s language styles in using words in songwriting have 13 aspects: 1) colloquial language, 2) rhyme words, 3) insertion words, 4) word duplication, 5) emotional words, 6) puns, 7) word segmentation, 8) archaic words, 9) dialects, 10) Word coinage, 11) word order, 12) word combinations, and 13) different word class. Moreover, using sentences has three aspects: 1) using affirmative sentences, 2) using imperative sentences, and 3) using interrogative sentences. Also, there are eight aspects of using stylistic impressions:1) similes, 2) metaphors, 3) symbols, 4) hyperbole, 5) personification, 6) paradox, 7) oxymorons, and 8) rhetorical questions. The findings of this research explain that Thanakrit Panichwit’s songwriting emphasizes the use of language that can convey meaning. It is easy for listeners to understand the song’s mood. In addition, it also emphasizes the consistency between language and music, which makes music beautiful in both literature and musical arts.